Simulation in admissions interviews: applicant experiences and programmatic performance prediction - Wildermuth, Anne; Battista, Alexis; Anderson, LaKesha N (Canadian Medical Education Journal, 2024)
Background: Admissions interviews are frequently used to assess personal and interpersonal attributes required for successful medical practice. Using simulation in interviews to engage applicants in realistic medical scenarios to assess these attributes is novel. This study evaluates applicant perceptions of simulation within multiple mini-interviews (MMI) and reports on subsequent student program performance. Methods: Physician assistant (PA) program applicants were invited to complete an anonymous post-interview survey that included one free-response question about their admissions experience. We chose to qualitatively analyze the free-response question. Additionally, success metrics of students who experienced simulation-based MMI were compared to prior cohorts who were admitted using traditional interviews. Results: Applicants undergoing simulation-based interviews in MMI had decreased incidences of major professionalism events, greater on-time program progression, and similar board pass rates compared to applicants who experienced traditional interviews. Several themes, highlighting the applicants’ varied responses to the simulation-based MMI, emerged including showcasing strengths and passion, feelings of fairness, accessing program faculty, and impacts on certainty. Conclusions: The use of simulation in admissions interviews is a valuable tool for assessing an applicant’s personal attributes in a clinical setting. Applicants admitted using simulation had improved programmatic performance compared to applicants admitted using traditional interviews. Applicants’ perceptions of simulation in interviews are helpful when designing the admissions experience.